2012
DOI: 10.1016/j.jacc.2012.04.062
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Adverse Cardiac and Bleeding Events Following Noncardiac Surgery Relative to Antiplatelet Therapy in Patients With Prior Percutaneous Coronary Intervention

Abstract: Noncardiac surgery (NCS) may be required within the first year after percutaneous coronary intervention (PCI) in approximately 4% of patients and is the second most common reason for premature discontinuation of antiplatelet therapy (APT),which may, in turn, increase the risk of perioperative ischemic events, particularly stent thrombosis. Its continuation may increase the risk of perioperative bleeding. We review current information on the incidence of these events, particularly related to APT, describe poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…A recent meta‐analysis has shown that patients on clopidogrel who have a hip fracture can be managed by normal protocols with early surgery (Soo et al , ). However, the same may not be true for DAPT, which is associated with significantly more surgery‐related bleeding (14·7%) compared to aspirin (4·1%) (Singla et al , ). This bleeding risk has to be balanced against the considerable increased thrombotic risk associated with premature termination or interruption of anti‐platelet monotherapy (Biondi‐Zoccai et al , ) or DAPT (Mehran et al , ; Rossini et al , ), which may be required to facilitate a surgical or other invasive procedure.…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…A recent meta‐analysis has shown that patients on clopidogrel who have a hip fracture can be managed by normal protocols with early surgery (Soo et al , ). However, the same may not be true for DAPT, which is associated with significantly more surgery‐related bleeding (14·7%) compared to aspirin (4·1%) (Singla et al , ). This bleeding risk has to be balanced against the considerable increased thrombotic risk associated with premature termination or interruption of anti‐platelet monotherapy (Biondi‐Zoccai et al , ) or DAPT (Mehran et al , ; Rossini et al , ), which may be required to facilitate a surgical or other invasive procedure.…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…As in a previous heparin study (18), the frequency of significant bleeding was not thought to exceed that which is commonly accepted (6).…”
Section: Discussionmentioning
confidence: 83%
“…However, data regarding the administration of heparin in this period are scarce, and the value of perioperative heparin therapy remains to be elucidated (2,(6)(7)(8)16). Some prior reports concluded that heparin bridging therapy might be ineffective because some degree of platelet inhibition seemed to be required to prevent stent thrombosis (6). Furthermore, other reports have indicated an association between perioperative cardiac events and the administration of unfractionated heparin (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with coronary stents requiring aggressive antiplatelet therapy represent a major challenge given the risks of perioperative bleeding and intra-stent thrombosis [16]. Patients with pulmonary hypertension (PH) also deserve special consideration given the increased right ventricular load resulting from one-lung ventilation and surgical resection.…”
Section: Cardiac Assessmentmentioning
confidence: 99%